Development of Porosity and Copper(II) Ion Adsorption Capacity by Activated Nano-Carbon Xerogels in Relation to Treatment Schemes - Badie S. Girgis; Mohamed N. Alaya; Iman Y. El-Sherif; Amina A. Attia; Nady A. Fathy (Adsorption Science & Technology)
In this study, activated nano-carbon xerogels were obtained by different activation schemes of a resorcinol–formaldehyde xerogel (RFX) with a resorcinol/catalyst (R/C) ratio of 50. For the precursor (RFX), activation was carried out under physical (steam) and chemical (H 3 PO 4 , KOH or NaOH) treatment in a one-stage process. Carbon xerogels were derived by simple pyrolysis at 500 °C or 700 °C for comparative purposes. The samples were characterized by different techniques including CHO elemental analysis, transmission electron microscopy (TEM) and nitrogen adsorption studies at 77 K, with the data obtained in the latter case being analyzed using the BET equation and the α S -method, as well as the fractal dimension approach. The porosities of the obtained carbons were considerably enhanced by chemical activation (mostly within the micropore range), while steam activation promoted the porosities to a lesser extent. Single-bottle removal of copper(II) ions was found to be appreciable in the case of the carbon xerogels (Q ads = 32–52 mg/g) and excellent with the activated carbon xerogels (Q ads = 76–198 mg/g). Application of the pseudo-second-order relationship gave the best fit to the kinetic uptake curves for selected samples. Activated carbon xerogels proved to be potential cation-exchange carbons whose performance appeared to be governed by the total surface area, slurry pH and the abundance of oxygen functional groups per unit surface area of the sorbent.